Being unempathic will make your loved ones feel lonelier: Loneliness in an evolutionary perspective. (1st October 2017) - Heatley Tejada, Ana; Montero, María; Dunbar, Robin
Abstract: Loneliness has been conceptualized as an alarm against social isolation under an evolutionary theoretical framework. Loneliness, as an adaptive feature, would have to be linked to environmental conditions and not only to the subjective evaluation of our social network. This research investigates lack of received empathy as an environmental trigger of the loneliness alarm. Lack of received empathy could explain previously observed correlations between loneliness and low satisfaction with social relationships, attachment insecurity, and certain age groups like teenagers and the elderly. A well-defined evolutionary model opens up new possibilities for the development of more efficient strategies to reduce loneliness. Highlights: A specific environmental cue for loneliness as an evolutionary alarm is proposed. Received empathy is tested under experimental and cross-sectional designs. Loneliness decreases as received empathy increases. The received empathy model shows better results than previously studied variables.